The epidemiology of Sarcocystis spp. in cattle of Western Australia. - Savini, G. (Cambridge University Press, 1992)
Oesophagus samples from 714 cattle from Western Australia were examined by artificial digestion to detect the presence of Sarcocystis spp. The overall prevalence of infection was 52%. The prevalence of infection increased with age and was highest in the entire males (92%). The prevalence was lower in cattle which originated from arid and semiarid regions (9 and 31% respectively) than those from tropical (87%) and temperate (60%) regions. Possible reasons for these differences are discussed and it is concluded that environmental and management factors as well as host age and sex influence the prevalence of infection with Sarcocystis spp. in cattle.